SOSIALISASI PENGELOLAAN SAMPAH ORGANIK BERBASIS SUMBER DENGAN PEMBUATAN “TEBE MODERN” PADA PESERTA DIDIK SMP DHARMA PRAJA BADUNG - Suanda, I Wayan; Rusmayanthi, Kadek Intan; Sumada, I Made; Alit, Dewa Made (Universitas Ngurah Rai, 2024)
The management of waste produced by community households is not yet optimal, especially the handling of organic waste. To reduce the negative impact of organic waste whose management is not optimal, community service is carried out in the form of education and socialization of the application of organic waste processing by creating